Valoración de la condición aeróbica del corredor de orientación a pie de alto nivel espanol - Sainz Fernández, L.; Rabadán Ruiz, M. (Archivos de medicina del deporte, 2013)
Purpose: Foot orienteering diff ers from other running events both in its cognitive element and in the type of terrain encountered. Some aspects of the fi tness required for orienteering may diff er from track and cross country running. The aim of this study was to assess the orienteer´s aerobic conditioning. Methods: Ten male orienteers (age 20,3 ± 5,6 years) participated in the study. They performed a maximal incremental treadmill test with pulmonary ventilation and respiratory gas exchange measures. Results: The average values were: Maximal oxygen uptake (VO2max): 70,2 ± 5,8 ml/kg.min; VO2 at the first ventilatory threshold (VT1): 49,5 ± 3,9 ml/kg.min (70,8% of VO2max); VO2 at the second ventilatory threshold (VT2): 61,2 ± 6,7 (87,1% of VO2max); Heart rate (HR) at VT1: 158,4 ± 4,8 lat/min (84% of maximal HR measured in the test); HR at VT2: 176,8 ± 6,7 lat/min (93,7% of maximal HR measured in the test). Conclusion: Elite orienteers have highly developed oxygen transport and utilization systems and perform at a high percentage of their VO2max for prolonged periods. Laboratory physiological assessment is considered fundamental in profiling orienteers, assess their physical conditioning and in providing data that are helpful in development of individualized training prescriptions to improve orienteering performance